غوغل كلاس رووم وتأثير استخدامه في تعليم مهارة القراءة - Iswara, Dana; Wahab, Muhbib Abdul; Albantani, Azkia Muharom; Hudatullah, Ruwaida; Farihin, Farihin (Kalimatuna: Journal of Arabic Research, 2022)
The objectives of this research are to detect the impact of the use of Google Classroom on the results of learning students’ substantive reading skills at this school, and to analyse the supporting and inhibiting factors in its use. After the researcher's pretest and postest of the students, received the pretest with the largest results 65 and the smallest results 40 and the average 50.  And posttest got the biggest results 80 and the smallest results 55 and average 68 and  got N-gain 0,6 at the good grade level. The researcher analyzed the data by law (T-test) with the help of SPSS 21 obtained Sig value. (2-tailed) 0,000 below 0,05 the alternative hypothesis H_a accepted the original hypothesis H_0 rejected. The conclusion of this research is that the teaching process using Google Classroom for students in this school has a statistically significant effect on the results of learning the reading skill.